2023
DOI: 10.1021/acsami.3c04733
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Epigallocatechin Gallate Enhances Therapeutic Effects of 3D-Printed Dermal Scaffolds in Mitigating Diabetic Wound Scarring

Abstract: Morbid dermal templates, microangiopathy, and abnormal inflammation are the three most critical reasons for the scarred healing and the high recurrence rate of diabetic wounds. In this present study, a combination of a methacrylated decellularized extracellular matrix (ECMMA, aka EM)-based hydrogel system loaded with copperepigallocatechin gallate (Cu-EGCG) capsules is proposed to fabricate bio-printed dermal scaffolds for diabetic wound treatment. Copper ions act as a bioactive element for promoting angiogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 64 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Thereupon, the photothermal conversion efficiency (η) of CG NSs was calculated to be 40.83% (Figure S3f), which was significantly higher than most common photothermal agents including amino-functionalized molybdenum disulfide nanosheets (NMNSs) (37.9%), Au nanoshells (13.0%), Au nanorods (21.0%), DSPN5 (30.8%), and so forth. Additionally, studies have reported that the combination of gallic acid and Cu ions exhibits antibacterial, antioxidant, and anti-inflammatory properties. , These results manifested the great potential of using such CG NSs as a PTT material for killing bacteria and accelerating wound healing under NIR laser irradiation. CA, a plant-based compound, is usually regarded as a natural antibacterial agent, which can effectively inhibit bacterial growth by inhibiting bacterial efflux pumps, reducing biofilm formation, inhibiting microbial ATPase, and inhibiting microbial activity .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Thereupon, the photothermal conversion efficiency (η) of CG NSs was calculated to be 40.83% (Figure S3f), which was significantly higher than most common photothermal agents including amino-functionalized molybdenum disulfide nanosheets (NMNSs) (37.9%), Au nanoshells (13.0%), Au nanorods (21.0%), DSPN5 (30.8%), and so forth. Additionally, studies have reported that the combination of gallic acid and Cu ions exhibits antibacterial, antioxidant, and anti-inflammatory properties. , These results manifested the great potential of using such CG NSs as a PTT material for killing bacteria and accelerating wound healing under NIR laser irradiation. CA, a plant-based compound, is usually regarded as a natural antibacterial agent, which can effectively inhibit bacterial growth by inhibiting bacterial efflux pumps, reducing biofilm formation, inhibiting microbial ATPase, and inhibiting microbial activity .…”
Section: Resultsmentioning
confidence: 94%
“…Additionally, studies have reported that the combination of gallic acid and Cu ions exhibits antibacterial, antioxidant, and anti-inflammatory properties. 36,37 These results manifested the great potential of using such CG NSs as a PTT material for killing bacteria and accelerating wound healing under NIR laser irradiation. CA, a plant-based compound, is usually regarded as a natural antibacterial agent, which can effectively inhibit bacterial growth by inhibiting bacterial efflux pumps, reducing biofilm formation, inhibiting microbial ATPase, and inhibiting microbial activity.…”
Section: ■ Introductionmentioning
confidence: 90%
“…Moreover, the composite scaffold demonstrated excellent hemostatic effect and hemocompatibility, thus showing an essential potential in skin engineering. Hu et al reported a multifunctional dECM-MA-based 3D printing hydrogel scaffold embedded with copper epigallocatechin gallate nano-capsules for diabetic wound management ( Hu et al, 2023 ). The cellular experiments indicated that the multifunctional 3D platform showed favorable anti-inflammatory capacity and good biocompatibility, which could accelerate vascularization and promote cell migration and invasion.…”
Section: Introductionmentioning
confidence: 99%